THE POTENTIAL IMPACT OF CURRENCY RISK ON BANK PERFORMANCE - Amalia Pradita; Ira Geraldina (International Journal of Accounting, Finance and Business, 2019)
The purpose of this study is to investigate the potential impact of currency risk on banks performance in Indonesia. This study uses transaction and translation gain or loss divided by total asset to measure currency risk, while banks performance is measured by return on asset (ROA). This study also uses 29 commercial banks that are listed in Indonesia Stock Exchange for the period 2014-2018 and has 133 observations as final sample. Using panel data analysis, this study finds that transaction risk as proxies of currency risk have significant impact on the financial performance of commercial banks in Indonesia, while translation risk as proxies of currency risk do not have significant impact on the financial performance of commercial banks in Indonesia. Meanwhile, this study finds that credit risk, operational risk and interest rate has negative impact on banks performance and capital risk and bank size has positive impact on banks performance. The result of this study has implication that high risk high return for banks performance.